P880 High incidence of inflammatory bowel disease in Northern Australia: a prospective community population-based Australian incidence study in the Mackay-Isaac-Whitsunday region. (30th January 2023) - Flanagan, A; O'Connor, S; Allsop, S; Tobin, J; Pretorius, C; Brown, I; Bell, S; Daveson, A J
Abstract: Background: The Mackay-Isaac-Whitsunday region encompasses 173, 892 people within a 400 km (250mile) radius in Queensland, Australia. We aimed to determine the incidence of Inflammatory Bowel Disease (IBD) in this region in northern Australia (-21.14°S) and to allow a comparison with southern Australian and New Zealand data (Geelong, Australia -38.14°S; Tasmania -41.43°S and -42.88°S [Launceston and Hobart] and Canterbury, New Zealand -43.46 °S). Methods: A prospective observational community population-based IBD study was conducted between 1 June 2017 and 31 May 2018. Primary outcome measures include the crude annual incidence rate of IBD, Crohn's disease (CD), Ulcerative colitis (UC) and infammatory bowel disease unspecified (IBDU), while secondary outcomes includes disease phenotype and behaviour. All new cases were identified through primary health care referrals and public and private hospital referrals into the clinic. All new cases of IBD were prospectively defined using rigorously recognised and accepted criteria and categorised using the Montreal Classification. Results: Fifty-six new cases of IBD were identified. Twenty-three were CD, 30 were UC and 3 were IBDU. The crude annual incidence rate per 100 000 for IBD, CD, UC and IBDU was 32.2 (95% confidence interval (CI): 24.78–41.84), 13.23 (95% CI: 8.79– 19.90), 17.25 (95% CI: 12.06–24.67) and 1.73 (95% CI: 0.56–5.35). When directly age-standardised to the World Health Organisation Standard Population Distribution, the overall CD, UC and IBDU incidence were 13.19, 17.34 and 1.85 per 100 000, with an overall age-standardised IBD incidence of 32.38. Conclusion: This is the first study to define the incidence of IBD in a Northern Australian cohort and to allow a comparison between North and Southern Australia. The IBD crude is the highest reported in Australia. Like others, we found a high and low incidence of upper gastrointestinal Crohn's disease and complicated disease at diagnosis respectively, likely reflective of the increased availability and early uptake of endoscopic procedures.